DIFFERENCES ON THE MOTION KNOWLEDGE LEVEL AT THE MALE STUDENTS IN SOME HIGH SCHOOLS IN THE REPUBLIC OF MACEDONIA - Viktor Mitrevski (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
With the research in this labour we want to realize the difference among the high school students` motion knowledge in different cities in Macedonia. This research consists of 135, 15 years old examinees, all students in high school, Ist class, divided into 3 sub samples The classification was made according the number of the classes and the number of the students who regularly attend the tuition. The analysis on the motorics level was conducted on the polygon for checking the psychophysical alertness of the students. For the differences` determination among the students` groups were used uni variant analyses of variable (ANOVA) and post hock analyses (LSD test). From the gained results we can notice that there are many differences among the students` groups on the motion level.